Transient and Cycle Structure of Elementary Rule 150 with Reflective Boundary - Akin, Hasan; Siap, Irfan; Koroglu, Mehmet E. (AMER INST PHYSICS, 2012)
Cellular automata are simple mathematical representation of complex dynamical systems. Therefore there are several applications of cellular automata in many areas such as coding, cryptography, VLSI design etc. [1, 2]. In this study, a recurrence relation for computation minimal polynomial of rule matrix of linear elementary rule 150 with reflective boundary condition is obtained. Then, the maximum transient and cycle lengths of this rule are calculated by algorithm in [3].
Keywords: Cellular automata; Reflective boundary; Transient and cycle lengths; CELLULAR-AUTOMATA; Mathematics; Physics